Awareness and use of heated tobacco products among adult smokers in six European countries: findings from the EUREST-PLUS ITC Europe Surveys. (12th September 2020) - Maria Lotrean, Lucia; Trofor, Antigona; Radu-Loghin, Cornel; Eremia, Marius; Mihaltan, Florin; Driezen, Pete; Kyriakos, Christina N; Mons, Ute; Demjén, Tibor; Fernández, Esteve; Katsaounou, Paraskevi A; Przewoźniak, Krzysztof; et al.
Abstract: Background: The study assessed awareness and use of heated tobacco products (HTPs) and factors that influenced these issues among cigarette smokers from six European countries in 2016 (Wave 1) and 2018 (Wave 2). Methods: A survey was conducted among a nationally representative sample of cigarette smokers aged 18 years or older from Germany, Greece, Hungary, Poland, Romania and Spain in 2016 ( N = 6011) and 2018 ( N = 6027; 53% of smokers from the previous wave were retained, regardless of smoking status and dropouts were replaced by a replenishment sample of smokers). Data were collected through face-to-face interviews. Estimates were produced using weighted data. The study presents the cross-sectional results. Results: Awareness of HTPs increased from 8% to 17% between the two waves. At Wave 1, 1.1% of the smokers declared having used HTPs at least once during their lifetime; and at Wave 2, this increased to 1.9% (around 1% or less in four countries, except for Greece and Romania where it was around 4%). Factors associated with HTPs use among those who had ever heard about these products at Wave 1 were country of residence, being a daily cigarette smoker and ever use of electronic cigarettes. At Wave 2, ever use of HTPs was significantly higher among those who had tried to quit smoking combustible cigarettes in the last 12 months, had tried electronic cigarettes during lifetime and perceived HTPs as less dangerous than combustible cigarettes; the country of residence was also associated with HTPs use. Conclusion: This study offers insights into the behaviours and perceptions of European adult smokers regarding HTPs, an important emerging issue in the field of tobacco control.